Reflections on Conducting Photographic Elicitation Interview in Sport Psychology Research in Indonesia - Rahayuni, Kurniati (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
Visual research method (VRM) is one of the widely used qualitative in social sciences, including in sport and exercise and particularly in the field of sport psychology. Photographic Elicitation Interview (PEI) is visual research involving photo-elicitation to generate interviews, which is still rarely used in sport and exercise research in Indonesia. Due to the dearth of literature and research using PEI in sport psychology, a review and reflections would be suitable to inform briefly about the emergent method. This paper will briefly explain: 1) VRM as a method in sport and exercise psychology research; 2) to inform what and how to utilise PEI as a part of VRM also its ethical considerations and procedures; 3) To inform reflections, challenges and opportunities the use of PEI in the Indonesian context. As conclusion, VRM and PEI are promising methods of qualitative data collection in sport and exercise research in Indonesia.Â